Pelatihan Hidroponik Tenaga Surya Sebagai Media Pembelajaran Pada Siswa SMP Muhammadiyah 5 Karanggeneng - Dini Makrufah; Muhammad Azwar Annas; Dwi Indah Setyo Pratiwi; Tegar Sabilliah; Hariono Hariono (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
In Indonesian education system, junior high schools have an important role in the growth and development of students who are in the teenage age range. Therefore, a community service program was carried out, Solar Hydroponic Training as a Learning Media for Muhammadiyah 5 Karanggeneng Middle School Students. This activity aims to train students at SMP Muhammadiyah 5 Karanggeneng in optimally utilizing the school environment's natural resources by managing solar powered hydroponic plantations, which in the process can become an effective student learning medium to increase students' insight and skills. This training was carried out for 4 months with various training methods which included counseling, demonstrations and direct practice carried out during the implementation process which included the socialization stage, seeding training, system installation and transplanting, cultivation assistance, harvest & post-harvest assistance and evaluation. The target of this activity is all students of SMP Muhammadiyah 5 Karanggeneng, totaling 42 students with the assistance of 2 teachers. During implementation, this program has achieved all the specified targets, including the establishment of a hydroponic green area that can be managed by students, which in the process has increased students' knowledge about hydroponic concepts and renewable technology, this is supported by the results of direct evaluations with teachers. companion along with the results of a comparison of post test and pretest scores which were quite significant.